Etnografi Komunikasi Ritual Tingkeban Neloni dan Mitoni Studi Etnografi Komunikasi Bagi Etnis Jawa di Desa Sumbersuko( )Kecamatan Gempol kabupaten Pasuruan - M. Rifa'i (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2017)
Tingkeban is a customary tradition of the community in Java for generations which indirectly can increase the confidence of a mother and father candidate to keep praying to be blessed with a sholehih baby branch and sholihah, that is with some ritual behavior done by society, basically is praying to get closer to Allah SWT. The purpose of this research is to see the communication of tingkeban neloni and mitoni rituals that occur in the community In Sumbersuko district Gempol Pasuruan regency. In this study the authors use qualitative methods of study of communication ethnography, because this method can describe, explain, and build relationships of categories and data found. This is in line with the objectives of the study of communication ethnography, to describe, analyze, and explain the communication behavior of one social group. The subject of the research is the seven monthly event consisting of three people and two people who understand and understand the meaning of the seven monthly event. Subject chosen by purposive sampling. The results of the research findings that seven-monthly ritual communication is a ritual activity performed at home or at home from parents of fathers or mothers, and attended by neighboring relatives and village communities Sumbersuko. Communicative events in seven-monthly rituals, topics, functions and objectives, settings, participants, message forms, message content, sequence of actions, interaction rules and norms, Whereas in communicative activities such as who knows and comprehends the implementation of seven monthly events is the host in seven monthly (tingkeban).